2010
DOI: 10.5713/ajas.2010.90480
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between MHC-DRB1 Gene Polymorphism and Hydatidosis in Kazakh Sheep

Abstract: The objective of this work was to analyze the relationship between ovine major histocompatibility complex (MHC) DRB1 gene polymorphism and genetic resistance to hydatidosis in Kazakh sheep. The Ovar (ovine MHC) class II DRB1 second exon was amplified by polymerase chain reaction (PCR) from DNA samples of 702 Kazakh sheep, including 302 sheep with hydatidosis and 400 health controls. PCR products were characterized by the restriction fragment length polymorphism (RFLP) technique using five restriction enzymes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…That study compared the frequency of genotypes in hydatidosis-infected sheep with those of the control group. Their results showed that there was a positive and significant correlation between identified genotypes and resistance to hydatidosis (28). In the present study, variation in the exon 2 sequence of the DRB1 locus was studied in Iranian Makuie sheep by PCR-RFLP analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That study compared the frequency of genotypes in hydatidosis-infected sheep with those of the control group. Their results showed that there was a positive and significant correlation between identified genotypes and resistance to hydatidosis (28). In the present study, variation in the exon 2 sequence of the DRB1 locus was studied in Iranian Makuie sheep by PCR-RFLP analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Allele DRB1* 0403 and DRB1* 07012, identified in the Columbia, Polypay, and Rambouillet breeds, were positively correlated with lower OPP provirus levels. In Kazakh sheep, by using the RFLP technique, 14 alleles and 28 genotypes were detected (28). That study compared the frequency of genotypes in hydatidosis-infected sheep with those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Al-Ghoury determined that HLA-DR1, 8 and DR-52 are associated with resistance and that HLA-DR 16 is associated with susceptibility to EG infection in Yemeni patients [34] . Li reported that susceptibility to alveolar Echinococcosis (A.E) was significantly associated with HLA-DR4 and that the DR7 allele might confer protection against A.E in humans [35,36] .…”
Section: Discussionmentioning
confidence: 99%
“…Since immunological events involved in the clinical course of a variety of diseases, information on MHC mRNA expression has involved in human disease, such as rheumatoid arthritis (Kerlan-Candon et al 2001), ankylosing spondylitis ), allergic vasculitis (Wang et al 2007), as well as ovine disease like lymphoid interstitial pneumonia (Woodall et al 1997). However, no systematic study has been reported on MHC genes expression in different stages of CE infection in sheep, although we previously reported that MHC genes associated with CE resistance or susceptibility in Kazakh sheep (Li et al 2010). This present study, therefore, was designed to investigate the dynamic changes of MHC-DQB1 mRNA expression in peripheral blood lymphocytes (PBLs), in Chinese merino sheep infected with Echinococosus granuclosus.…”
Section: Introductionmentioning
confidence: 96%
“…Since CE represents a considerable economic and public health significance, it is, therefore, of great importance to control the disease. And during the past decades, studies pertaining to the immunological control of CE have received much more attention (Wen and Craig 1994;Sturm et al 1995;Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%